Keys to staying sharp: A randomized clinical trial of piano training among older adults with and without mild cognitive impairment - Hudak, Elizabeth M; Bugos, Jennifer; Andel, Ross; Lister, Jennifer J; Ji, Ming; Edwards, Jerri D (Contemporary clinical trials, 2019)
BACKGROUND: The prevalence of dementia, the most expensive medical condition (Kirschstein, 2000 and Hurd et al., 2013 [1,2]), and its precursor, mild cognitive impairment (MCI) are increasing [3]. Finding effective intervention strategies to prevent or delay dementia is imperative to public health. Prior research provides compelling evidence that central auditory processing (CAP) deficits are a risk factor for dementia [4-6]. Grounded in the information degradation theory [7, 8], we hypothesize that improving brain function at early perceptual levels (i.e., CAP) may be optimal to attenuate cognitive and functional decline and potentially curb dementia prevalence. Piano training is one avenue to enhance cognition [9-13] by facilitating CAP at initial perceptual stages [14-18]. OBJECTIVES: The Keys To Staying Sharp study is a two arm, randomized clinical trial examining the efficacy of piano training relative to music listening instruction to improve CAP, cognition, and everyday function among older adults. In addition, the moderating effects of MCI status on piano training efficacy will be examined and potential mediators of intervention effects will be explored. HYPOTHESES: We hypothesize that piano training will improve CAP and cognitive performance, leading to functional improvements. We expect that enhanced CAP will mediate cognitive gains. We further hypothesize that cognitive gains will mediate functional improvements. METHOD: We plan to enroll 360 adults aged 60 years and older who will be randomized to piano training or an active control condition of music listening instruction and complete pre- and immediate post- assessments of CAP, cognition, and everyday function.
Keywords: muzikoterapie; sebeuplatnění; Humans; neuropsychologické testy; Everyday functional performance; Music Therapy; lidé středního věku; Music training; Mild cognitive impairment; kognice; Self Efficacy; Female; Aged; Cognitive intervention; Auditory Perception; senioři; lidé; randomizované kontrolované studie jako téma; Piano training; Neuropsychological Tests; ženské pohlaví; Male; Randomized Controlled Trials as Topic; Middle Aged; Cognitive Dysfunction; výzkumný projekt; Aged, 80 and over; senioři nad 80 let; klinické zkoušky, fáze II jako téma; Research Design; mužské pohlaví; Cognition; kognitivní dysfunkce; Central auditory processing; Activities of Daily Living; sluchová percepce; Clinical Trials, Phase II as Topic; činnosti denního života